MODERN PRINCIPLES OF FORMING THE PROFESSIONAL ETHICS OF FUTURE SOCIAL WORKERSAT UNIVERSITIES - Zozulyak-Sluchyk Rоksolyana (Mountain School of Ukrainian Carpaty, 2019)
The formation of specialists in the social sphere at the present stage of Ukraine's formation puts radically new demands and challenges in front of the educational sphere. Higher education is responsible for it. Special attention should be paid to the new research approaches to the theoretical substantiation of the specific principles of the formation of professional ethics and morals O. Dub, A. Kalensky, M. Mikhnyuk, L. Moskalova, O. Ponomarenko, N. Sopneva, L. Horuzhoy and others who form the basis of a professional -ethical reflection in the ethics-applied field. The article reveals and substantiates specific, general pedagogical and general-didactic principles of the process of formation of professional ethics of future social workers at universities. Social work as a type of professional activity is also built on specific principles, such as humanism, social responsiveness, communicative, variability of social assistance, client centricism, personal approach, trust in the client, and maintaining customer trust in a social worker, justice, tolerance, modality (flexibility), permanence (continuity), competence, confidentiality, mediation, etc. Formation of professional ethics of future specialists in social work in the educational process of universities will be successful when it will be based on such specific principles: professional axiological orientation; the unity of the theory of professional ethics and moral practice (professional morality); systematic formation of professional ethics; interdisciplinary in the formation of professional ethics; the unity of moral consciousness and moral activity; complementarity; integration and mutual influence of ethical and professional knowledge; designing of personal trajectory of formation; moral and ethical reflexive orientation of the process of teaching students of the specialty "Social Work"; moral choice; facilitation; academic integrity. Important are the general pedagogical principles: humanization and democratization, scientific, continuity, dynamism, personal activity. Also, the professional development of specialists at universities is influenced by general-diplomatic principles: objectivity, connection theory with practice, systematic, visibility and variety of methods, strength of learning knowledge, skills and abilities. Thus, the effectiveness of the process of forming the professional ethics of future specialists in social work is ensured by systematic interaction and complementary, general-didactic, general pedagogical and specific principles. They take into account moral and ethical norms of professional activity, professional culture and various educational forms of study at the university.